2022
DOI: 10.1007/s10787-022-01096-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral melatonin in patients with severe COVID-19: a randomized controlled trial

Abstract: Patients with COVID-19 have shown melatonin deficiency. We evaluated the efficacy and safety of administration oral melatonin in patients with COVID-19-induced pneumonia. Patients were randomly assigned in a 1:1 ratio to receive melatonin plus standard treatment or standard treatment alone. The primary outcomes were mortality rate and requirement of IMV. The clinical status of patients was recorded at baseline and every day over hospitalization based on seven-category ordinal scale from 1 (discharged) to 7 (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…The aim was to determine if any single study was responsible for the significant results observed. After excluding either the study by Ameri et al (32) or Alizadeh et al (13), the pooled relative risk decreased significantly from 0.72 to 0.31. However, we did not observe any noticeable decrease in heterogeneity during the one-by-one exclusion process.…”
Section: Sensitivity Analysesmentioning
confidence: 84%
See 2 more Smart Citations
“…The aim was to determine if any single study was responsible for the significant results observed. After excluding either the study by Ameri et al (32) or Alizadeh et al (13), the pooled relative risk decreased significantly from 0.72 to 0.31. However, we did not observe any noticeable decrease in heterogeneity during the one-by-one exclusion process.…”
Section: Sensitivity Analysesmentioning
confidence: 84%
“…The average age of the patients was above 55 in two studies (13,15), and below 55 in the other three studies (29, 31, 32). The severity of COVID-19 in the enrolled patients was severe in three studies (13,15,32).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective randomized clinical trial of severe COVID-19 in Iraq, 82 patients were administered melatonin (standard therapy plus 10 mg melatonin daily for two weeks), while 76 patients were provided standard therapy only; the melatonin-treated group presented less thrombosis and sepsis events after adjusting for other confounding factors and lower mortality (melatonin group vs. control group: 1.2% vs. 17.1%) [ 168 ]. In another randomized controlled trial of melatonin treatment for hospitalized Iranian patients with severe COVID-19, a total of 109 patients in the melatonin group (adjuvant 5 mg melatonin twice daily for 7 days) and 117 patients in the control group (standard therapy only) were enrolled in the study [ 169 ]. The mortality rate was 67% in the melatonin group compared with 94% in the control group.…”
Section: Melatonin and Covid-19mentioning
confidence: 99%
“…Further favorable effects of melatonin receptors in the COVID-19 context are their synchronizing effect on biological rhythms and their sleep-initiating properties that might be beneficial for intensive care patients suffering from disrupted sleep patterns or sleep deprivation, which favors the production of inflammatory cytokines and predisposition to lung inflammation [ 30 ]. First results from clinical trials on the effect of melatonin in critically ill patients with SARS-CoV-2 infection report a significantly improved clinical status when given as an adjunctive agent in combination with basic treatments in some studies but not in others without any apparent adverse events (Ref) [ [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%